Simple-minded behavior - Grabowski, Damian; Skorupka, Alfred (Folia Philosophica, 2004)
This work presents a construct: a «simple-minded behavior», which consists of the following features: spontaneity, creativity, empathy, trust and emotional response. Simpleminded behavior is characteristic of both a simple-minded man [acc. to J. Bańka] and a selfrealizing man [acc. to A.H. Maslowj. This construct is thus an axis of similarities between philosophy and psychology. This article presents the results of empirical research into simple-minded behavior and a questionnaire of simple-mindedness. The researches proved that simple-minded behaviors are associated with a feeling of inner control. It is likely that simplemindedness is conducive to inner-controllability and vice versa - a feeling of inner control is conducive to simple-minded behaviors.